2017
DOI: 10.1177/2158244016687345
|View full text |Cite
|
Sign up to set email alerts
|

Condom Usage Negotiation Among Customarily Married Women in Katlehong, Johannesburg

Abstract: South Africa has the highest number of HIV-infected people in the Southern African Region, and of great concern is the fact that cases of new infections among young people, especially young women and girls, are on the increase. The prevalence of HIV and deaths caused by AIDS are still on the increase, whereas condom use, particularly in rural areas, remains low. Consistent condom use is central to the prevention of unwanted pregnancies, HIV, and other sexually transmitted infections (STIs); yet, young men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…A couple of studies have conducted an objective assessment of HIV infection in examining associations of IPV within voluntary counselling and STI clinics with women's HIV infection and have revealed that HIV infection among women was elevated by experiencing violence from their partners [27,28]. Similarly, some qualitative studies have illustrated how an inability to negotiate for a safer sex in HIVnegative individuals result in their increased risk of HIV infection by experiencing IPV [29][30][31][32]. Chin (2013) in his study using a set of nationally representative data in sub-Saharan Africa shows how the risk of domestic violence is affected by exogeneous increase in HIV prevalence among women in a cluster.…”
Section: Introductionmentioning
confidence: 99%
“…A couple of studies have conducted an objective assessment of HIV infection in examining associations of IPV within voluntary counselling and STI clinics with women's HIV infection and have revealed that HIV infection among women was elevated by experiencing violence from their partners [27,28]. Similarly, some qualitative studies have illustrated how an inability to negotiate for a safer sex in HIVnegative individuals result in their increased risk of HIV infection by experiencing IPV [29][30][31][32]. Chin (2013) in his study using a set of nationally representative data in sub-Saharan Africa shows how the risk of domestic violence is affected by exogeneous increase in HIV prevalence among women in a cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Others attribute the low prevalence of condom use to neglect of this group in the promotion of consistent condom use [ 10 ]. In some studies that were conducted in South Africa, marriage was found to be a barrier to condom use, which may relate to the desire of the couples to have children, making negotiating condom use difficult [ 11 , 12 ]. Studies reporting a low prevalence of condom use among married couples include one that was conducted among married and cohabiting women in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies that have incorporated a diagnostic testing of HIV infection while examining the associations of HIV infection with IPV among women within voluntary testing or STI clinics, have demonstrated an elevated HIV infection among women who have experienced violence from partners (Chandrasekaran, Krupp, George, & Madhivanan, 2007;Fonck, Els, Kidula, Ndinya-achola, & Temmerman, 2005). Data from qualitative studies illustrate how an HIV-negative person experiencing IPV may be at increased risk of HIV infection because of an inability to negotiate safer sex (Dube, Nkomo, & Khosa, 2017;Go et al, 2003;Karamagi, Tumwine, Tylleskar, & Heggenhougen, 2006;Stevens & Richards, 1998). Chin (2013) in his study in sub-Saharan Africa found that the HIV epidemic can affect the risk of spousal violence in ways other than as a direct stressor.…”
Section: Introductionmentioning
confidence: 99%